The effect of applying Bloom’s taxonomy theory of education in the teaching of evidence-based medicine curriculum for undergraduates - WANG Yunyun; YUAN Shuai; WANG Yu; LI Binghui; FANG Cheng; ZHANG Yuanyuan; HUANG Jiao; ZENG Xiantao (Yixue xinzhi zazhi)
Objective Exploring the application effect of Bloom's taxonomy theory of education in the teaching of evidence-based medicine curriculum.Methods Undergraduate students majoring in clinical medicine (5, 5+3) and basic medicine at the Second School of Clinical Medicine of Wuhan University in 2019 were selected as the research subjects. The Bloom's taxonomy of educational objectives was implemented, and a self-made questionnaire was used to investigate their mastery of relevant knowledge content, changes in attitudes, and course satisfaction.Results 75 students were included in the study. After the course, the correct rate of students' understanding of evidence-based medicine, Meta-analysis, experimental design, and other related knowledge ranged from 54.67% to 100.00%, all were significantly higher than those before the course, and the differences before and after the course were statistically significant (P